Analysis of the implementation of standard operating procedures and their impact on production efficiency in MSMES in bantan subdistrict - Damanik, M. A. Jaya (Junal Ilmu Manajemen, 2025)
This study aims to analyze the implementation of Standard Operating Procedures (SOPs) and their impact on operational efficiency in small and medium enterprises (SMEs) engaged in food processing in Bantan Subdistrict, Medan. Operational efficiency is a critical factor for sustainability and competitiveness, particularly for SMEs in highly dynamic urban markets. The research employs a quantitative descriptive method with data collected through structured questionnaires and in-depth interviews with 30 SME owners. Key indicators of operational efficiency examined include production time, cost per unit, daily output, and error rates. Data analysis is conducted using linear regression to measure the relationship between SOP implementation levels and operational performance. The results show a significant positive correlation between the application of SOPs and improved production efficiency. Moreover, SMEs that applied written SOPs demonstrated lower production costs and fewer process errors compared to those without structured procedures. However, the study also identifies barriers such as limited managerial knowledge, lack of training, and resistance to change. These findings suggest the need for government-supported training programs and institutional facilitation to encourage formal SOP adoption in SMEs. The study contributes to the literature by highlighting the importance of operational formalization in enhancing SME performance and provides practical insights for local economic policy and SME development strategies.